Analisis Preferensi Dan Rute Destinasi Pariwisata Pantai Di Daerah Istimewa Yogyakarta - Widyastuti, Henny; Marsoyo, Agam; Setiawan, Bakti (Jurnal Tata Kota dan Daerah, 2018)
The mainstay tourism destinations in Yogyakarta Special Region are beach tourism destinations. Accessibility in beach tourism destinations does not deter tourists. The purpose of this study is to illustrate the relationship between accessibility to preferences and routes of beach tourism destinations, and identify factors affecting the preferences and routes of beach tourism destinations in Yogyakarta Special Region. The method used is deductive method with quantitative analysis. The analysis method used is using descriptive statistical analysis. The result of the analysis shows that there is a relation between accessibility with preference and route of beach tourism destination. There are beach tourism destinations that are often bypassed and become the referral of Baron Beach and Parangtritis Beach. Factors influencing the preferences and routes of beach tourism destinations are (i) the socio-demographic factor of tourists, consisting of the area of origin of tourists, the source of information, and the frequency of travel, (ii) the amenity factor which includes the availability of tourism facilities and infrastructure and the ability of facilities and infrastructure tourism in meeting the needs of tourists, (iii) tourist behavior factor, consisting of tourist destinations, tourism motivation, and tourist expectations of tourism facilities and infrastructure needed, (iv) tourist attraction factors that include the ability of tourist attractions in attracting tourists, tourist attractions are popular tourists, and tourist activities undertaken by touristsKeywords: Preferences, Routes, Beach Tourism Destinations, Yogyakarta Special Region.